2015
DOI: 10.1007/s10826-015-0214-7
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensionality of Racial/Ethnic Socialization: Scale Construction for the Cultural and Racial Experiences of Socialization (CARES)

Abstract: Negotiating racial politics in the United States is a rapidly transforming and dynamic matter. As a result, racial/ethnic socialization (R/ES) measurement must match this transformation to reflect the current processes utilized by Black Americans to manage racial conflict. We describe the scale construction of the Cultural and Racial Experiences of Socialization (CARES), a multidimensional assessment of R/ES based on Racial Encounter Coping Appraisal and Socialization theory. Additionally, we tested the CARES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Particularly noteworthy was the attention to construct and context specificity in these new instruments. For instance, Ayón () developed a measure of cultural socialization with attention to the unique needs and experiences of Latino immigrant families, Juang et al () took a similar approach but with a focus on Asian American families, and Bentley‐Edwards and Stevenson () developed a measure to capture the multifaceted nature of ethnic–racial socialization messages (e.g., cultural insights, racial stereotyping, racial protection) for Black youth. In a similar vein, two measures of familial ethnic–racial socialization specific to the context of transracial adoption emerged.…”
Section: Methodological Advances and Insightsmentioning
confidence: 99%
“…Particularly noteworthy was the attention to construct and context specificity in these new instruments. For instance, Ayón () developed a measure of cultural socialization with attention to the unique needs and experiences of Latino immigrant families, Juang et al () took a similar approach but with a focus on Asian American families, and Bentley‐Edwards and Stevenson () developed a measure to capture the multifaceted nature of ethnic–racial socialization messages (e.g., cultural insights, racial stereotyping, racial protection) for Black youth. In a similar vein, two measures of familial ethnic–racial socialization specific to the context of transracial adoption emerged.…”
Section: Methodological Advances and Insightsmentioning
confidence: 99%
“…Although many ethnic‐racial socialization approaches have been conceptualized across the literature (Bentley‐Edwards & Stevenson, ; Brown & Krishnakumar, ), Hughes et al. () comprehensive review identified four prominent dimensions that are frequently considered across studies: cultural socialization, preparation for bias, promotion of mistrust, and egalitarianism.…”
Section: Ethnic‐racial Socialization and Child Developmentmentioning
confidence: 99%
“…In contrast, the long history of legalized racism and discrimination against African Americans in the United States has resulted in many African American parents engaging in racial socialization mechanisms by which they transmit information, values, and perspectives about race and ethnicity to their children (Bentley-Edwards & Stevenson, 2015;Hughes et al, 2006;Rogers, 2001). As a result, African American youth may be more keenly aware of the structural barriers to educational and social mobility based on one's race and racial identity (Sanchez & Awad, 2015) and may be prepared for discriminatory treatment when it occurs (Seaton et al, 2008).…”
mentioning
confidence: 99%